The Effect of Combination of E-glass and Polyethylene Fiber-Reinforced Composites on Flexural Strength - Ahmed Mohamed Abubaker Abdulazeez; Aesa Alzaroug Jaber; Widowati Siswomihardjo; Siti Sunarintyas; Abdulhadi Warreth (Journal of Medical Sciences, 2023)
The Fiber-reinforced Composites (FRCs) is a combination of fibers and a resinous matrix. The mechanical properties of (FRCs) materials are primarily dependent upon fiber type (glass, carbon, aramid, or polyethylene). The aim of this study was to evaluate the effect of combination of E-glass and Polyethylene (FRCs) on flexural strength. Materials and Method: This research was an experimental study and using braided Polyethylene (pre-Silanated) fiber (Construct, KerrLab, Corporation, West, Collins Orange, CA, USA), unidirectional E-Glass fiber (everStick C& B, Stick Tech Ltd, Turku, Finland), Resin matrix (Construct Resin), (Construct, KerrLab, West, Collins Orange, CA, USA) and Coupling agent 3-(Trimethoxysilyl) propyl methacrylate (γ-MPS) 98% Purity (Acros organics Pittsburgh USA). This study was conducted with sixteen specimens which were prepared in a metallic mold (25 x 2 x 2 mm). The specimens were divided into four groups according to the type of the Fiber and combination of fibers. (N = 4): G1 - Two layers of (PE-EG-FRCs); G2 - Two layers of (PE-PE-FRCs); G3 - Two layers of (EG-EG-FRCs); G4 - Two layers of (EG-PE FRCs). Measurement of flexural strength used the universal testing machine. The result was analyzed with one way Anova. Result: The result of the study showed that the flexural strength for PE-EG fiber was 240.47±3.78 MPa and 179.25 ±42.47 MPa for EG-PE, 175.13±22.56 MPa for EG-EG, and 154.69 ±16.91MPa for PE-PE. The result of one way Anova test shows there were significant differences among groups in the effects on flexural strength because the value of (F = 8.377, p value < 0.01). For each group, values for flexural strength were obtained. PE-EG fiber was the highest flexural strength (p < 0. 05), when compared to other evaluated combinations. Two layers of PE-EG appear to be more resistant than other combination of (FRCs).